Qualitative-quantitative research methodology : exploring the interactive continuum - Newman, Isadore (Southern Illinois University Press, 1998)
Rejecting the artificial dichotomy between qualitative and quantitative research strategies in the social and behavioral sciences, Isadore Newman and Carolyn R. Benz argue that the two approaches are neither mutually exclusive nor interchangeable; rather, the actual relationship between the two paradigms is one of isolated events on a continuum of scientific inquiry.